The novel orthosteric agonist M1 muscarinic acetylcholine receptor reveals anti-Alzheimer’s disease activity - Maryam Taheri; Maryam Afzali Mehr; Hossein Ghafouri (Scientific Reports)
Abstract Cholinergic treatments with an emphasis on M1 muscarinic acetylcholine receptor (mAChR) agonists as potential modulating agents are a new approach in Alzheimer’s disease (AD) therapy. In previous research, we designed and characterized novel thiazolidine-2,4-dione (TZD)-derived compounds that possess anti-AD properties and enhance the expression of mAChRM1 in rats. This study evaluated a novel orthosteric agonist of mAChRM1 from related pathways that has shown promising anti-Alzheimer’s disease activity. PC12 cells were exposed to various concentrations of TZ4M before they were exposed to scopolamine (3 µM). Immunocytochemistry and western blot analyses revealed that TZ4M increased the expression of mAChRM1 in differentiated cells induced by scopolamine-treated PC12 cells. The results showed that TZ4M (3 and 5 µM) markedly upregulated PKC and ChAT protein expression, and the cells were significantly protected against increased ROS levels followed by neuronal cell loss, as evidenced by the MTT assay. TUNEL staining indicated that TZ4M impeded the shaping of apoptotic bodies. Analysis of the amino acid sequences of the ligand–protein binding site indicated that TZ4M is bound to the orthosteric site (acetylcholine site). This study revealed that TZ4M, a derivative of TZD, effectively protects against scopolamine-induced damage. TZ4M, a novel mACRM1 orthosteric agonist, is promising for treating AD.